2022
DOI: 10.3390/biom12010145
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and Biochemistry Aspects of the 4-Hydroxy-2,3-trans-nonenal

Abstract: 4-hydroxy-2,3-trans-nonenal (C9H16O2), also known as 4-hydroxy-2E-nonenal (C9H16O2; HNE) is an α,β-unsaturated hydroxyalkenal. HNE is a major aldehyde, formed in the peroxidation process of ω-6 polyunsaturated fatty acids (ω-6 PUFAs), such as linoleic and arachidonic acid. HNE is not only harmful but also beneficial. In the 1980s, the HNE was regarded as a “toxic product of lipid peroxidation” and the “second toxic messenger of free radicals”. However, already at the beginning of the 21st century, HNE was perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 86 publications
(94 reference statements)
0
8
0
Order By: Relevance
“…The nitric oxide and peroxynitrite molecules contribute to protein tyrosine nitrosylation [ 26 ], which was observed in our study ( Figure 1 ). On the other hand, numerous initiators of lipid peroxidation, such as 4-HNE in biological systems, are often hydroxyl radical (OH • ), ozone (O 3 ), nitrogen oxide (NO) and dioxide (NO 2 ), and sulfur dioxide (SO 2 ) [ 51 ]. This may result from the downregulation of LPO, MPO, and SOD3.…”
Section: Discussionmentioning
confidence: 99%
“…The nitric oxide and peroxynitrite molecules contribute to protein tyrosine nitrosylation [ 26 ], which was observed in our study ( Figure 1 ). On the other hand, numerous initiators of lipid peroxidation, such as 4-HNE in biological systems, are often hydroxyl radical (OH • ), ozone (O 3 ), nitrogen oxide (NO) and dioxide (NO 2 ), and sulfur dioxide (SO 2 ) [ 51 ]. This may result from the downregulation of LPO, MPO, and SOD3.…”
Section: Discussionmentioning
confidence: 99%
“…Like above mentioned, Peng et al ( 42 ) observed decreased unsaturated fatty acids metabolism in MCF-7 xenograft mice, which is consistent with our result. Accumulated evidence has demonstrated that n-6 unsaturated fatty acids such as linoleic acid ( 43 , 44 ) and arachidonic acid ( 45 , 46 ) have an important role in cancer cell growth and apoptosis. Therefore, we think that the increased unsaturated fatty acids in PTX and MBL extract treated group may help induce tumor cell apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, the lipid peroxidation process involves the reaction of oxygen and hydrogen radicals with PUFAs, resulting in the formation of LOO • and reactive aldehyde species that are formed as a secondary product of the peroxidation cycle. Thus, due to their stability and highly reactive properties, these byproducts may impair biochemical processes leading to aggravated metabolic function [ 36 , 37 ]. Beyond lipid peroxidation products, free radicals can react with proteins and lead to the formation of advanced glycation end products (AGEs).…”
Section: Lipid Peroxidation Biomarkersmentioning
confidence: 99%